Time Reversal Imaging of Ultrasonic Pitch-Catch Measurements Based on Decoupled Wavefields in Cased Hole - LI Meng; WANG Hua; LI Jiale; MU Ruoyao (Cejing jishu)
Cased-hole ultrasonic pitch-catch logging serves as a critical quantitative detection method in cement bond evaluation, primarily employed for the quantitative assessment of bonding quality at both casing-cement and cement-formation interfaces. Conventional reverse time migration (RTM) with coupled acoustic field cross-correlation imaging conditions often generates significant artifacts near real reflection interfaces. These artifacts arise from the complex characteristics of formation interface reflections in actual acquisitions, containing multiple seismic phases, which consequently interfere with accurate identification of the true cement-annulus-formation interface. To address this challenge, this study proposes a Helmholtz decomposition-based methodology. The approach establishes an improved RTM imaging method for cased-hole ultrasonic flexural waves through wavefield decoupling of both forward and backward propagated wavefields at each timestep, incorporating decoupled wavefield auto-correlation and cross-correlation operations. Synthetic case studies demonstrate that the auto-correlation RTM results of decoupled S-wave fields exhibit enhanced energy concentration at theoretical reflection interfaces when the annular medium is conventional cement, accompanied by significant reductions in imaging artifacts and noise. Therefore, the proposed decoupled wavefield RTM method provides an effective solution for high-precision imaging of cement-annulus-formation interfaces in cased-hole measurement environments.